Personality traits and job performance among academic staff in a private academic institution - Lim Lee Ping; Ong Choon Hee; Tan Owee Kowang; Chi-Hua Wu (Institute of Advanced Engineering and Science, 2024)
This study investigates the association between the personality traits of academic staff members and their job performance in a Malaysian private educational institution. The personality traits were based on the Big Five model, which has five dimensions: openness to experience, conscientiousness, extraversion, agreeableness, and neuroticism. About 110 participants from this institution were surveyed using a quantitative questionnaire, and their data were gathered. Throughout the study, the data were examined utilizing multiple regression analysis and factor analysis. According to the study’s findings, conscientiousness, and openness to experience significantly positively affect job performance. However, it was determined that extraversion, agreeableness, and neuroticism were not statistically significant and had no connection to job performance. As a result, in this institution, openness to experience is the most essential predictor of job performance. The findings of this study showed the management that openness to experience and conscientiousness are crucial for improving job performance inside the institution. Therefore, the management should pay more attention to these areas and recruit new employees with openness to experience and conscientious personality traits.